Propuesta Metodológica para la Modernización de la Personería Municipal de Santiago de Cali - Trejos Trejos, Lina María; Zabala, Paola Andrea (Universidad Icesi, 2013)
This project of degree has like objective to propound a methodology that contributes to the modernization at Municipal Personeria in Santiago de Cali, under the Colombian normative parameters for public entities, using modern management tools. The technical study was conducted through three methodologies: Comparative analysis with another entity, the organizational model of WEISSBORD on six boxes, and the DOFA analysis, what allowed us to establish the need that has the entity to carry out a transformation that adapts by itself to the legal changes, so as to the political, social, economic, and technological developments that have emerged in the last five years. Furthermore, the methodology for the proposed modernization of the personality builds on existing regulations established in the guide the proposed modernization of public institutions established by the Administrative Department for Civil Service (DAFP) and includes management tools of modern with a major emphasis on services. Its development has been formulated in four phases: 1. Sensitization; 2. External and internal analysis of the organization, 3. Process of functional structuring for entity, and 4 Identify of the staff required for the implementation and execution of the processes, and the specific manuals for tasks and responsibilities.
Con el presente proyecto de grado se pretende plantear una propuesta metodológica que contribuya a la transformación o modernización de la Personería Municipal de Santiago de Cali, bajo los parámetros normativos que rigen en Colombia a las entidades públicas sumado a la aplicación de criterios propios de la administración. Para este propósito, se realizó un estudio técnico bajo 3 metodologías: análisis comparativo con otra entidad, el modelo organizacional de seis casillas de WEISSBORD y el análisis interno y externo (DOFA), que permitió establecer la necesidad que tiene la entidad de realizar una transformación que se adapte a los cambios legales, políticos, sociales, económicos y tecnológicos surgidos en los últimos cinco años. De otra parte, la metodología utilizada para la propuesta de modernización de la personería toma como base la normatividad vigentes consolidada en la guía la propuesta de modernización de entidades públicas establecida por el Departamento Administrativo para la Función Pública (DAFP), incorporando a su vez herramientas de administración de moderna orientada al servicio. El desarrollo de esta propuesta se plantea en cuatro etapas: 1. Sensibilización, 2. Análisis externo e interno, 3. Proceso de estructuración funcional de la entidad, y 4. El manual especifico de funciones y competencias.
Keywords: T658.001/T787p; Facultad de Ciencias Administrativas y Económicas; Producción intelectual registrada - Universidad Icesi; Administración; Competencias laborales; Modernización del Estado; Personería municipal - Colombia; Administrative Modernization; Public Institutions